Repellency Effect of Essentials Oils Using K and D Module against Aedes aegypti, Vector of Dengue and Chikungunya - Uniyal, Ashish; Tikar, Sachin N.; Shukla, Shakti V.; Agrawal, Om P.; Sukumaran, Devanathan; Veer, Vijay (Indian Forester, 2015)
Essential oils are natural volatile substances from plants and they are used as protective measure against blood-sucking insects. The objective of the study was to determine the effective repellency of 23 essential oils at various doses against female mosquitoes Aedes aegypti under laboratory conditions using K&D module and to identify chemical constituents of the oils by Gas Chromatography/Mass Spectrometry (GC/MS). The results showed that litsea oil exhibited effective mean percentage repellency of 43%, 86%, 93% and 100% at 0.01%, 0.1%, 1.0% and 10% concentration, respectively with the median effective dose (ED50 ) of 0.012 (95% CI= 0.003-0.028). At 20% concentration, litsea oil showed 83% repellency upto 2 hr and the dominant component of litsea oil was identified as Zcitral by GC/MS. The studies indicate that these oils could be used in the preparation of herbal mosquito repellents which are safe to human beings.